SOME STUDY RESULTS ON THE CHARACTERISTICS AND VARIABILITY OF WATER MASSES IN THE SOUTH CENTRAL VIETNAM - Thai, To Thai (Vietnam Journal of Marine Science and Technology, 2019)
Study on the characteristics and variability of water masses has great practical significance in determining the original of water bodies for the most general view of the hydrodynamics in that area. This also helps in comprehensive research and water partition according to the set of natural conditions to serve the rational exploitation of marine resources and environmental protection. The study on the water masses in the South Central Vietnam has been carried out by many scientists and has quite detailed results in the characteristic of water mass in this area, but the results are mainly based on measured data of salinity-temperature up to 2006. Although the distribution of data is relatively good, but the systemization and synchronization are limited. In this paper, based on updating the newly observed data from many projects in recent years such as Vietnam-Russia (2011), Vietnam-USA (2013, 2015), and basic projects in the Institute of Oceanography (2016, 2017), the results have identified the origin of surface water masses in the study area from the East Vietnam Sea, the Western Pacific Ocean and the Java Sea. In addition, we have also seen changes in the number of water masses and the structure of the water mass changes in characteristics such as temperature, salinity, and depth of their existence during ENSO